Fabrication of Force Sensor Circuits on Wearable Conductive Textiles. (2015) - Usma, C.; Kouzani, A.Z.; Chua, J.J.C.; Arogbonlo, A.; Adams, S.; Gibson, I.
Abstract: This paper discusses design and fabrication processes in the development of a wearable and flexible conductive resistive sensor. The design and development of the sensor involve the use of Sn-Ag-Cu (SAC)plated Nylon fabric, precisionfused deposition modeling(FDM) using silicone and petrolatum for etch-resistant masks using the EnvisionTEC GmbH Bioplotter, and wet etching using Chromium, Ammonium Persulphate, and Salt-Vinegar etching solutions. Preliminary testing with other mask types, development processes, and sensor design approaches for various applications are discussed.